Experience with Large Fiscal Adjustments - Horton, Mark (Occasional Papers; Occasional Paper ;, 2006)
When policymakers have little option but to consider a sizable fiscal adjustment, they are confronted by the following questions: Can a large fiscal adjustment be implemented succesfully? How is a large adjustment best designed and implemented? What will be its impact on the economy? This Occasional Paper addresses these questions by describing the experience of countries that have undertaken large fiscal adjustments in the last three decades. It provides operational guidance to policymakers by identifying preconditions, common policy approaches, and institutional arrangements underlying successful and unsuccessful adjustment episodes.